Intergovernmental councils and centralization in Australian federalism - Phillimore, J.; Fenna, Alan (2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group This paper explores how a high level of vertical intergovernmentalism and a low level of horizontal intergovernmentalism reflect as well as contribute to a high degree of centralization in Australian federalism and in the role and activity of intergovernmental councils (IGCs). Pre-eminent among the latter is the Council of Australian Governments (COAG), which sits at the apex of a system of ministerial councils and attendant agencies. Policy coordination is the principal motivation behind the Commonwealth’s use of COAG. The States established their own horizontal body in 2006 but that faded quickly in an experience that confirmed the underlying realities of Australian federalism.